2016
DOI: 10.1002/anie.201600007
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Axinellamines A and B

Abstract: Axinellamines A and B are broad-spectrum anti-bacterial pyrrole–imidazole alkaloids that have a complex polycyclic skeleton. A new asymmetric synthesis of these marine sponge metabolites is described herein, featuring an oxidative rearrangement and an anchimeric chlorination reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…[42] Despite the high catalytic activity, the AgFoam 60 electrode requires a high overpotential of 0.88 V relative to the CO 2 /CO equilibrium potential of À0.11 V vs RHE. In retrospect, anodized Ag (92 % at À0.6 V), [28] oxide-derived Ag (89.5 % at À0.8 V), [8] de-alloyed nanoporous Ag (92 % at À0.6 V) [30] and nanocoral Ag catalyst (95 % at À0.6 V) [43] display very high catalytic performance for the conversion of CO 2 to CO at lower overpotentials. Nonetheless, the AgFoam 60 electrode may be favoured for potential scaling up for large scale applications due to its facile fabrication and moderately high catalytic performance in delivering high Faradaic efficiency (94.7 %) and mass specific CO current density (2.84 A g À1 ) at an applied potential of À0.99 V ( Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[42] Despite the high catalytic activity, the AgFoam 60 electrode requires a high overpotential of 0.88 V relative to the CO 2 /CO equilibrium potential of À0.11 V vs RHE. In retrospect, anodized Ag (92 % at À0.6 V), [28] oxide-derived Ag (89.5 % at À0.8 V), [8] de-alloyed nanoporous Ag (92 % at À0.6 V) [30] and nanocoral Ag catalyst (95 % at À0.6 V) [43] display very high catalytic performance for the conversion of CO 2 to CO at lower overpotentials. Nonetheless, the AgFoam 60 electrode may be favoured for potential scaling up for large scale applications due to its facile fabrication and moderately high catalytic performance in delivering high Faradaic efficiency (94.7 %) and mass specific CO current density (2.84 A g À1 ) at an applied potential of À0.99 V ( Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of such observation, it is understood that rate determining step for the AgFoam 60 electrode is the initial transfer of one electron to a CO 2 molecule to form the *CO 2 C À intermediate adsorbed (* represents surface adsorbed species) to the surface. [8,30,41] Therefore, it is conjectured that the high performance of the AgFoam 60 electrode for CO 2 RR is due to the greater stabilization of the rate determining *CO 2 C À radical intermediate on the active sites present in the high index facets that is present in the highly porous three dimensional electrode compared to Ag foil. Similar conclusion was also reported with the nanoporous Ag catalyst where the high catalytic performance was attributed to the greater active sites present in the high index faceted curved catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The h-CuS MCs exhibits a Tafel slope of 124 mV dec À1 , which is close to the theoretical calculated value, [38] indicating that the initial electron transfer for CO 2 activation is the rate-determining step for the overall electrocatalytic process. [31] Additionally, Figure 5c shows that the Tafel slope of h-CuS MCs increased at higher potential, which indicated that CO 2 reduction is limited by mass transport at the overpotential above 0.4 V (vs. RHE). Therefore, at a higher overpotential, the h-CuS MCs may have a stronger surface binding to *H and a rather lower concentration *CO 2 * À intermediates, which make the formation of H-H bond becomes a dominant pathway in a higher overpotential.…”
Section: Resultsmentioning
confidence: 90%
“…The large overpotential required for the CO 2 RR can be attributed to the barrier of the initial electron transfer to a CO 2 molecule. [30][31][32][33][34] Herein, we reported a hydrothermal method for the synthesis of Cu 2 O microcubes (Cu 2 O MCs), which then converted into hollow CuS microcubes (h-CuS MCs) by ionic exchange reaction. The as-prepared h-CuS MCs, benefitting from its unique structure and enhanced exposed edge sites, show a significantly improved electrocatalytic activities and selectively toward electrocatalytic reduction conversion of CO 2 to CO.…”
Section: Introductionmentioning
confidence: 99%